2010
DOI: 10.1007/s11046-010-9362-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Cercospora kikuchii Isolates From Soybean Cultured in Argentina as Revealed by Molecular Markers and Cercosporin Production

Abstract: Leaf blight and purple seed, caused by the fungal pathogen Cercospora kikuchii (Matsumoto & Tomoyasu) M. W. Gardner are very important diseases of soybean (Glycine max L. Merr.) in Argentina. The aims of this work were: (a) to confirm and to assess the genetic variability among C. kikuchii isolates collected from different soybean growing areas in Santa Fe province using inter simple sequence repeats (ISSR) markers and sequence information from the internal transcribed spacer (ITS) region of rDNA and (b) to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
7
0
3
Order By: Relevance
“…Several lines of evidence suggest etiological anomalies in CLB and PSS. In population genetic studies, an array of markers–AFLP, RAPD, and DNA sequences from a single or few loci–suggested remarkable differences in genetic structure among populations, distribution of pathogenicity ‘groups’ or ‘lineages’, and uneven prevalence throughout the Americas [ 15 , 18 , 19 ]; some of those lineages were absent from Japan [ 20 ]. Besides, there were conflicting reports on isolate-dependent conditions for sporulation in vitro [ 21 ], and phenotypic variation among axenic cultures has been observed [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest etiological anomalies in CLB and PSS. In population genetic studies, an array of markers–AFLP, RAPD, and DNA sequences from a single or few loci–suggested remarkable differences in genetic structure among populations, distribution of pathogenicity ‘groups’ or ‘lineages’, and uneven prevalence throughout the Americas [ 15 , 18 , 19 ]; some of those lineages were absent from Japan [ 20 ]. Besides, there were conflicting reports on isolate-dependent conditions for sporulation in vitro [ 21 ], and phenotypic variation among axenic cultures has been observed [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…& Cooke (Martins et al, 2008), and C. kikuchii (Matsumoto & Tomoy.) Gardner (Almeida et al, 2005;Cai & Schneider, 2005;Lura et al, 2011). Conversely, C. zeae-maydis Tehon & Daniels and C. zeina Crous & Braun (originally reported as C. zeae-maydis Group I and Group II, respectively) (Wang et al, 1998;Dunkle & Levy, 2000;Okori et al, 2003;Crous et al, 2006) and C. sorghi Ellis & Everh.…”
Section: Resultsmentioning
confidence: 99%
“…However, at the late stage of peanut growth and development, peanut plants are infected by leaf spots which evidently reduce the yields. Genetic diversity of plant pathogen populations present in a particular locality is especially valuable to enhance epidemiological studies and implement effective control strategies (Lurá et al 2011).…”
Section: Discussionmentioning
confidence: 99%